2008
DOI: 10.1002/bem.20447
|View full text |Cite
|
Sign up to set email alerts
|

GSM base stations: Short‐term effects on well‐being

Abstract: The purpose of this study was to examine the effects of short-term GSM (Global System for Mobile Communications) cellular phone base station RF-EMF (radiofrequency electromagnetic fields) exposure on psychological symptoms (good mood, alertness, calmness) as measured by a standardized well-being questionnaire. Fifty-seven participants were selected and randomly assigned to one of three different exposure scenarios. Each of those scenarios subjected participants to five 50-min exposure sessions, with only the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
(32 reference statements)
2
21
0
5
Order By: Relevance
“…Two of these field intervention studies assessed the application of RF-EMF shielding [20,21], the third was based on randomly turning on and off a temporary constructed mobile phone base station [22]. In total, 709 non-EHS individuals and 102 EHS individuals were included in these six trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these field intervention studies assessed the application of RF-EMF shielding [20,21], the third was based on randomly turning on and off a temporary constructed mobile phone base station [22]. In total, 709 non-EHS individuals and 102 EHS individuals were included in these six trials.…”
Section: Resultsmentioning
confidence: 99%
“…In another study with 57 volunteers, RF-EMF exposure increased the ratings of the participants concerning their calmness [20]. Leitgeb et al [21] applied three exposure conditions (true shield, sham-shield, and control) to a collective of 43 EHS individuals during three nights each.…”
Section: Resultsmentioning
confidence: 99%
“…18 One field intervention study observed a small increase in calmness under unshielded conditions compared with shielded conditions, but no effect on mood or alertness. 33 In an observational study from Egypt, several symptoms were more prevalent in 85 inhabitants or employees of a house near an MPBS compared with 80 employees considered unexposed. 27 In an Austrian study with 365 participants, a statistically significant association was found between 3 out of 14 symptoms (headache, cold hands and feet, concentration difficulties) and MPBS exposure.…”
Section: Non-specific Symptoms Of Illhealthmentioning
confidence: 98%
“…31,39 Four epidemiological studies applied an experimental approach (field intervention) in which exposure was modified either by turning on and off an MPBS 28,29 or by using shielding curtains. 30,33 Sample size ranged from 43 to 26 039 participants. The cut-off values differentiating exposed from unexposed persons varied between 0.1 and 0.43 V/m.…”
Section: Non-specific Symptoms Of Illhealthmentioning
confidence: 99%
“…A szerzôk öt évvel késôbb készült újabb áttekintése -melyben további 15 provokációs kísérlet eredményeit dolgozták fel -sem eredményezett az elektromágneses expozíció és a tünetek közvetlen ok-okozati viszonyát támogató adatokat (Rubin és mtsai, 2010). Az eredmények ellentmondásosságát jól jelzi, hogy míg egy provokációs vizsgálat részt-vevôi intenzívebb mobiltelefon-bázisállomás-expozíció esetén fokozottabb nyugalomérzésrôl számoltak be (Augner, Florian, Pauser, Oberfeld, & Hacker, 2009), addig egy másik vizsgálatban mobiltelefon-szignálok jelenléte fokozott ingerlékenységgel társult az IEI-EMF-csoportban (Eltiti és mtsai, 2007). Ráadásul további két vizsgálatban az IEI-EMF-es személyek rosszabbul teljesítettek a valós és álmezôk megkülönböztetésében, mint kontrolltársaik, ami leginkább arra vezethetô vissza, hogy az elektroszenzitív csoport az álexpozíció során is gyakrabban tapasztalt fizikai érzeteket (Frick és mtsai, 2005; Landgrebe és mtsai, 2008).…”
Section: A Pszichogén Elmélet Bizonyítékaiunclassified